THE EFFECT OF ADDITION PHYTASE ENZYMES WITH DIFFERENT DOSES TO FEED ON THE GROWTH AND SURVIVAL RATE OF Hemibagrus nemurus WITH RECIRCULATION SYSTEM - Andreas Siahaan; Mulyadi Mulyadi; Niken Ayu Pamukas (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACTHemibagrus nemurus is one type of freshwater fish that is the mainstay of fisheries commodities in Riau Province. The presence of an anti-nutritional factor called phytic acid in feed causes less optimal utilization of feed protein. One effort to overcome this is by adding phytase enzymes in the feed so that it is expected to inhibit anti-nutritional substances and increase feed protein absorption. The research was carried out from October to November 2019 at the Aquaculture Technology Laboratory, Faculty of Fisheries and Marine, Riau University. This study aims to determine the effect and dose of phytase enzymes added to feed for growth and survival of baung. The method used was experiment of Completely Randomized Design (RAL) with one factor, four treatments and three replications. The treatment used P0: feeding with a dose of phytase enzyme 0 mg/kg, P1: feeding with a dose of phytase enzyme 500 mg/kg, P2: feeding with a dose of phytase enzyme 1000 mg/kg, P3: feeding with a dose of phytase enzyme 1500 mg/kg. The parameters observed were the absolute weight growth, absolute length, specific growth rate, feed efficiency, survival rate and water quality. The results showed that feeding with the addition of the phytase enzyme had an effect on the growth of baung fish. The best treatment was P2 (feeding with a dose of phytase enzyme 1000 mg/kg) with an absolute weight of 4.75 g, an absolute length of 2.22 cm, a specific growth rate of 1.90%, feed efficiency 77.86%, and a survival rate of 95. 55%. The results of water quality measurements during the study were temperature 26-27.3 oC, pH 6-7, DO 4.12-5.57 mg/L and ammonia 0.03-0.09 mg/L.Keywords: Hemibagrus nemurus, Phytase Enzyme, Phytic Acid, Growth, Survival Rate